The effect of a customized courseware on language performance of young students / Nazeri Mohamad Amin - Mohamad Amin, Nazeri (2008)
The positive effects of customized courseware on language performance of young students have been supported by research carried out by Nutta (1998) and Zhuo (1999) on post secondary school students. The present study, however, was conducted on the primary school students in Malaysia and a customized courseware was used. The study was undertaken to find out the effects of customized courseware on language performance of young students. The purpose of this study is to investigate whether teaching of grammar by using computer is more effective than teaching of grammar by using traditional method. The other purpose of the study is to investigate whether the effects of using computer as compared to using traditional method vary with the different grammatical items. The grammatical items under study were past tense, present tense, regular verb in past tense, irregular verbs in past tense, simple sentence in present tense and complex sentence in present tense. The population consisted of 40 students of year 5 in Sekolah Kebangsaan Institut Perguruan Kuala Terengganu, Kuala Terengganu and they were chosen based on quasi- experimental design. The study was done based on quasi-experimental research where two groups were assigned as a control group and an experimental group. Pretest and post test were administered on control group and experimental group by using a set of questions based on grammatical items under study. The findings were derived from the analyses of students' pretest and posttest scores. The result of this study indicated that the teaching of grammar by using computer is more effective than the teaching of grammar by using traditional method. The findings also indicated that the effects of teaching of the grammatical items by using computer vary compared to the teaching of the grammatical items by using the traditional method. In this research, the teachings of past tense and irregular verbs in past tense were more